A new isolation method for biomass-burning tracers in snow: Measurements of p-hydroxybenzoic, vanillic, and dehydroabietic acids. (December 2015) - Gao, Shaopeng; Liu, Dameng; Kang, Shichang; Kawamura, Kimitaka; Wu, Guangming; Zhang, Guoshuai; Cong, Zhiyuan
Abstract: Organic acids such as p -hydroxybenzoic, vanillic, and dehydroabietic acids are unique biomass-burning tracers for black carbon (BC) and dissolved organic carbon (DOC) in the snow of mountain glaciers, Arctic and Antarctic ice sheets. In this study, we developed a method by solid-phase extraction (SPE) coupled with gas chromatography/ion trap mass spectrometry for the determination of those organic acids in snow. The limit of detection (LOD) is 0.002, 0.001, 0.004 ng mL −1 for p -hydroxybenzoic, vanillic, and dehydroabietic acids, respectively. For p -hydroxybenzoic and vanillic acids, all the four SPE cartridges used produce good recoveries (>75%). However, for dehydroabietic acid, HLB cartridge has much better performance than DPA, FEP-2 and PAX cartridges. The method was applied to the snow samples collected from Zhadang Glacier in the Tibetan Plateau (TP), and demonstrated its feasibility in pretreating and detecting of these target compounds. We found that BC and DOC accumulated in the snow during winter and spring over the TP glaciers are mainly derived from biomass burning. This result demonstrates the capability of our analytical method for a deep understanding on the source of carbonaceous materials in snow. Highlights: A new measurement method for biomass-burning tracers in snow was developed. The method was successfully applied to the snow samples from Zhadang Glacier. BC and DOC in those glacial snow samples are mainly derived from biomass burning.